2017
DOI: 10.1038/srep43771
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin deficiency contributes to the development and progression of benign prostatic hyperplasia in obesity

Abstract: The incidence of benign prostatic hyperplasia (BPH) is increasing among obese individuals, but few studies have fully explained the underlying mechanisms. We aimed to elucidate the relationship between obesity and BPH. Herein, we show that in prostatic epithelial and stromal cells, adiponectin exerts multifunctional effects including anti-proliferation, blocking of G1/S-phase progression and the promotion of apoptosis via inhibiting the MEK-ERK-p90RSK axis. Furthermore, we found that a high-fat diet (HFD) led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
1
15
0
2
Order By: Relevance
“…Although the exact role of ERK is yet to be revealed in BPH, Papatsoris and Papavassiliou (2001) suggested the action of MAPK signaling as one of the molecular bases of BPH. Some studies, including our previous report, show that ERK is regulated in the enlarged prostate ( Fu et al, 2017 ; Xu et al, 2017 ; Youn et al, 2017 ) or proliferation of prostate stromal cells ( Zhang et al, 2008 ; Youn et al, 2017 ). Other studies report that the ERK cascade is phosphorylated in reaction to AR, leading to cell cycle progression in prostate cancer ( Peterziel et al, 1999 ; Migliaccio et al, 2000 ).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although the exact role of ERK is yet to be revealed in BPH, Papatsoris and Papavassiliou (2001) suggested the action of MAPK signaling as one of the molecular bases of BPH. Some studies, including our previous report, show that ERK is regulated in the enlarged prostate ( Fu et al, 2017 ; Xu et al, 2017 ; Youn et al, 2017 ) or proliferation of prostate stromal cells ( Zhang et al, 2008 ; Youn et al, 2017 ). Other studies report that the ERK cascade is phosphorylated in reaction to AR, leading to cell cycle progression in prostate cancer ( Peterziel et al, 1999 ; Migliaccio et al, 2000 ).…”
Section: Introductionmentioning
confidence: 81%
“…Although several other studies also showed that the MAPK pathway is closely related to cell proliferation in prostate cancer ( Papatsoris et al, 2007 ; Rybak et al, 2015 ), the exact role of MAPK signaling pathway in BPH is yet to be cleared. Especially, ERK signaling is a considerable interest in BPH because our and other previous studies showed that the ERK signaling is activated in BPH conditions in vivo and in vitro ( Zhang et al, 2008 ; Fu et al, 2017 ; Xu et al, 2017 ; Youn et al, 2017 ). In consistent with such reports, our findings indicate that ERK is dramatically activated under BPH conditions and subsequently returned to normal levels by BBR treatment, but phosphorylation levels of JNK and p38 were not significantly affected in BPH-induced rats ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the association of BPH and adipokines (e.g., C-peptide, leptin and adiponectin) have reported conflicting results [6][7][8]. To the best of our knowledge, there are no reports of a relationship between omentin and BPH.…”
Section: Backgroudmentioning
confidence: 92%
“…Adiponectin was also found to have anti-proliferation effects on prostatic cancer cells [111]. Adiponectin induces cell cycle arrest of prostatic epithelial and stromal cell lines and induces apoptosis by increasing caspase-3 and downregulating of Bcl2 (B cell lymphoma) gene [112].…”
Section: • Prostate Cancermentioning
confidence: 97%